New strategy of improving the dispersibility of acrylamide-functionalized graphene oxide in aqueous solution by RAFT copolymerization of acrylamide and acrylic acid. (August 2019) - Jin, Tao; Yin, Hong; Easton, Christopher D.; Seeber, Aaron; Hao, Xiaojuan; Huang, Chunjie; Zeng, Rongchang
Graphical abstract: The preparation process and dispersion mechanism. Highlights: Amidation of GO with AM facilitates its ability to participate in polymerization. Water-dispersible GO was prepared by surface polymerization of AM and AA via RAFT. The grafted polymer chain length showed a great effect on GO dispersion stability. Abstract: Graphene Oxide (GO) is a very unique material with a broad potential. However, modifying GO effectively to achieve maximum dispersion stability in a medium is very critical for various applications. In this paper, GO/poly(acrylamide-co-acrylic acid) (PAM-co-PAA) composites (GMAs) were readily prepared by a two-step method. Firstly, acrylamide (AM) monomer was immobilized onto GO sheets through an amidation reaction, followed by copolymerization of acrylamide (AM) and acrylic acid (AA) on the surface of GO sheets in a second step via reversible addition-fragmentation chain transfer (RAFT) polymerization, GO-AM (GM) acting as a macro monomer to participate in the copolymerization. Characterization by Fourier Transform Infrared Spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) provided evidence for the successful polymerization of AM/AA on the surface of GM. Thermogravimetric analysis (TGA) revealed greater than 50 wt% grafting of PAM-co-PAA. X-ray diffraction (XRD) analysis showed that the d-spacing of the GO sheets increased with the introduction of the polymer. The morphological studies were performed by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscope (TEM), showing that a polymeric layer covered the surface of GO sheets. Compared to the original morphologies of GO sheets, the more disordered structures were attributed to the intercalation of polymer molecules into the spacing of the GO sheets and the reaction of functional groups on the surface of GO sheets. The dispersion stability test demonstrated that the reported facile method could generate GO-polymer hybrid nanomaterials stably dispersed in aqueous solution for more than 15 days, showing a great potential and practical applications for composite coatings.